2011
DOI: 10.4012/dmj.2010-084
|View full text |Cite
|
Sign up to set email alerts
|

Basic evaluation on physical properties of experimental fluorinated soft lining materials

Abstract: The purpose of the present study was to compare the properties required for the clinical application of soft lining materials containing a fluorinated monomer versus that of conventional materials in an effort to develop a new soft lining material with long-term stable viscoelastic properties. Four soft lining materials were examined. Two experimental materials containing dodecafluoroheptyl methacrylate (SR12F) or tridecafluorooctyl methacrylate (SR13F) were prepared. Two commercial soft lining materials, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 24 publications
2
28
3
2
Order By: Relevance
“…But the fluorinated experimental soft lining material containing a large amount of MDGMA has some shortcomings in water sorption, solubility and discoloration behaviors 16) . To improve these drawbacks in the material, a part of the monomer contents was replaced with fluorinated monomer, since in a previous fundamental study on the development of experimental soft lining materials, the materials containing fluorinated monomers with a large number of fluorine atoms in one molecule were found to exhibit large viscous flow, low water sorption and solubility and good staining resistance 16,23) . The silica powder was used as filler.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the fluorinated experimental soft lining material containing a large amount of MDGMA has some shortcomings in water sorption, solubility and discoloration behaviors 16) . To improve these drawbacks in the material, a part of the monomer contents was replaced with fluorinated monomer, since in a previous fundamental study on the development of experimental soft lining materials, the materials containing fluorinated monomers with a large number of fluorine atoms in one molecule were found to exhibit large viscous flow, low water sorption and solubility and good staining resistance 16,23) . The silica powder was used as filler.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the experimental material with the monomer including a large number of fluorine atoms in one molecule were not found to change its viscoelastic properties after storage in deionized water at 37±2°C for 1 week. These previous studies also suggested that fluorinated monomers such as 13FMA could be clinically applicable for soft lining materials 16,23) . Although reported experimental soft lining materials that contain fluorinated monomers show promising characteristics for clinical applications, the influence of the fluorinated monomer content on the viscoelasticity, water sorption and solubility have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Soft liners are also used for obturators after maxillofacial surgery or to increase retention in cases of bilateral undercuts [1,2]. In addition to viscoelasticity, there are several other requirements for soft liners, including high dimensional stability, color stability, tear resistance, biocompatibility with oral tissue and good adhesion to the denture base [3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…The fluorinated polymer 2-6F had approximately 3,000 of molecular weight. These components were chosen for use in the present study according to compositions used in a previous study 22) . In the present study, we prepared two groups of experimental soft lining materials with different compositions in order to examine the effects of the components.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development of a production process for fluoropolymer soft lining material that does not generate carbon tetrachloride was initiated [18][19][20] . In previous studies, experimental materials containing tridecafluorooctyl methacrylate, which can be synthesized without generating carbon tetrachloride, Effect of composition of experimental fluorinated soft lining materials on bond strength to denture base resin exhibited greater viscous flow, low water sorption, low solubility, and good staining resistance compared to commercial products 21,22) . Although the experimental fluoropolymer lining materials reported in these previous studies exhibit promising material characteristics for clinical application in the future, the adhesive properties of these experimental materials to the denture base remain unknown.…”
Section: Introductionmentioning
confidence: 99%